2019
DOI: 10.1108/idd-07-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

Do altmetrics correlate with citations? A study based on the 1,000 most-cited articles

Abstract: Purpose The purpose of this paper is to study the presence of highly cited papers of Nature in social media websites and tools. It also tries to examine the correlation between altmetric and bibliometric indicators. Design/methodology/approach This descriptive study was carried out using altmetric indicators. The research sample consisted of 1,000 most-cited articles in Nature. In February 2019, the bibliographic information of these articles was extracted from the Scopus database. Then, the titles of all ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
15
0
1
Order By: Relevance
“…Research impact can be addressed using different metrics and can also be affected by various determinants. Although some previous research found a positive correlation between traditional metrics and altmetrics [20,39], others claim they are weakly correlated [24]. Our study has also constated that the items influencing both metrics are different [29].…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Research impact can be addressed using different metrics and can also be affected by various determinants. Although some previous research found a positive correlation between traditional metrics and altmetrics [20,39], others claim they are weakly correlated [24]. Our study has also constated that the items influencing both metrics are different [29].…”
Section: Discussionsupporting
confidence: 43%
“…They capture the relevance of research based on metrics such as article views, downloads, and mentions on social media or news media [16], considering channels such as Twitter, Mendeley, CitedULike or blogging [18,19], among others. Given the growth and relevance of social media for sharing scientific knowledge [20], these novel metrics have become necessary and represent another way to assess research impact.…”
Section: Introductionmentioning
confidence: 99%
“…To date, various statistical analyses have been used to measure the correlation between citation count and the Altmetrics Attention Score. Among those statistical analyses, Costas et al, 2015;Huang, Wang, & Wu, 2018;and Ouchi, Saberi, Ansari, Hashempour, & Isfandyari-Moghaddam, 2019 have used Spearman's rank order correlation coefficient to measure the correlation between citation count and the Altmetrics Attention Score. Spearman's rank order correlation coefficient is a non-parametric statistical test that measures "the strength and direction of association that exists between two variables measured on at least an ordinal scale" (Laerd Statistics, 2018b).…”
Section: Discussionmentioning
confidence: 99%
“…They identified that AAS poorly correlated with citations and the correlation strength did not change on subgroup analyses of individual journal, study type, or the individual score components. Ouchi et al (2019) explored "the correlation between Altmetric and bibliometric indicators for 1000 most-cited articles in Nature. A positive significant correlation was found between the Altmetric indicators and citations".…”
Section: Related Literature 21 Correlation Between Altmetric Attention Score and Citationmentioning
confidence: 99%